Aphrodisiaca Activity of Momordica charantia L. and Areca catechu L. Ethanolic Extract Againts Blood Pressure and Body Weight of White Mile Rats - Sofia, Vivi; Aji, Abisyahdan Satria (FITOFARMAKA: JURNAL ILMIAH FARMASI, 2024)
Advances in the discovery of herbal medicine and the increasing popularity of traditional  medicines have made accessto traditional medicines in the market increasingly easier. Bitter melon and areca nut are known to have many benefits and potential as natural medicine. Previous studies has shown the aphrodisiac effects of these two natural ingredients. This research aimed to  determine the additional effects, particularly on blood pressure and body weight of rats, when bitter melon and areca nut are administered as aphrodisiacs. Test animal retrieval techniques based on complete randomized design (RAL). Blood pressure was measured using the CODA® instrument on 25 white rats divided into 5 treatment groups, namely the control group (CMC Na 0.5 % 0.5 % w/v), the bitter melon extract group at a dose of 280 mg / kg BW, the areca nut extract group at a dose of 50 mg/kg 50 mg / kg BW, the mixed  bitter melon and areca nut extracts group (1: 1), and the X-Gra® group. Blood pressure profiles measured included systolic and diastolic blood as well as changes in rat body weight before and after treatment. The results of the study of systole and diastole blood pressure parameters and rat body weight in groups I, II, III, IV, V analyzed using the Tukey HSD method obtained results that were not significantly different (sig 0.05) in all groups. Based on this study, it was concluded that the aphrodisiac activity of bitter melon and areca nut seeds did not significantly influence changes  in blood pressure, systole and diastole, and  body weight rats.